High Anger Expression is Associated with Reduced Cortisol Awakening Response and Health Complaints in Healthy Young Adults. (29th April 2016) - Romero-Martínez, Ángel; Moya-Albiol, Luis
Abstract: The extant evidence suggests a robust positive association between expression (anger expression-out) and suppression (anger expression-in) of anger and compromised health. Nevertheless, the underlying psychobiological mechanisms which explain these relationships are not well understood. This study examined whether anger expression would predict general health, cortisol awakening response (CAR) and evening cortisol levels in a community sample of 156 healthy young adults of both genders. Participants were distributed into two groups according to their anger expression scores: high and low anger expression (HAE and LAE, respectively). Findings indicated that those with HAE had worse self-reported health ( p = .02) and higher CAR than the LAE group ( p = .04). Moreover, high levels of anger expression-out ( p < .01) and -in ( p < .01, for all) predicted a worse self-reported health in both groups. On the other hand, high anger expression-out was associated with flattened CAR but only in the HAE group ( p < .01). This study reinforces the need to develop effective strategies to provide mechanisms to regulate anger expression by promoting personal growth and positive skills that enhance individuals' well-being and quality of life and, in turn, their own health.